Assessment of Forest Cover Changes in the Xe Pian National Park Using Geographic Information System and Remote Sensing Technologies - nanthepha, ketkeo; Linthasone, Thipphaphone; Seankham, Vanhtha (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
Xe Pian National Park in southern Lao PDR is an internationally important biodiversity hotspot; however, it has experienced increasing pressure from agricultural expansion, logging activities, and land encroachment. The absence of systematic and up-to-date spatial monitoring data has limited effective management and conservation planning. This study aims to (1) quantify forest cover changes during 2015, 2020, and 2025 using Geographic Information Systems (GIS) and remote sensing techniques; (2) analyze land use and land cover (LULC) change patterns and their driving factors, particularly in relation to encroachment and enforcement of protected area regulations; and (3) provide a scientific baseline to support sustainable forest management and policy development. LULC classification was conducted using Landsat-8 OLI and Sentinel-2 imagery with a Random Forest (RF) algorithm. The classification achieved high accuracy, with Overall Accuracy ≥ 86% and Kappa Coefficient ≥ 0.83. The results indicate a continuous decline in forest cover from 236,176.24 ha in 2015 to 216,014.70 ha in 2020, and further to 204,162.01 ha in 2025, representing a total loss of 32,014.23 ha (13.56%) over ten years. Spatial analysis revealed that agricultural land increased by 231.95% and grassland by 147.05%, largely within protected areas, indicating weak enforcement of conservation regulations. Trend projection suggests that if current deforestation rates continue, an additional 11,853 ha of forest may be lost by 2030. This would significantly threaten ecosystem integrity and biodiversity conservation in the park. The findings provide essential scientific evidence for improving land use planning, strengthening enforcement mechanisms, and establishing continuous monitoring systems for long-term sustainable management of Xe Pian National Park.